Effect of low frequency sound vibration on acute stress response in university students—Pilot randomized controlled trial - Kantor, Jiří; Vilímek, Zdeněk; Vítězník, Martin; Smrčka, Pavel; Campbell, Elsa A.; Bucharová, Monika; Grohmannová, Jana; Špinarová, Gabriela; Janíčková, Kateřina; Du, Jian; Li, Jiaoli; Janátová, Markéta; et al. (Frontiers in Psychology, 2022)
Background Low frequency sound (LFS, combined with music listening) is applied by practitioners in vibroacoustic therapy who report a positive effect of this intervention on acute stress response. However, there is a lack of research on this topic and studies with mainly objective measurements are scarce. Materials and methods In this pilot double-blinded Randomized Controlled Trial we used a multimodal approach to measurement of acute stress response in 54 international university students attending a university summer school in Olomouc, the Czech Republic who were individually randomized into a group receiving LFS vibration and a control group. In both groups, the acute stress response was measured by heart rate variability (HRV), visual analogue scales (VAS) for stress and muscle relaxation. Results Differences were found in pre-test post-test measures, however, between groups differences occurred only for HRV, with statistically significant improvement in the experimental group (parameter LF/HF and pNN50). Conclusion Vibroacoustic therapy has the potential to contribute to the stress management of university students. Further research is needed to explore the effect of LFS on stress response, especially when applied without additional music listening.